The Conflict Between the Meaning of a Word and Its Form: The Unity of Disunity - Król, Martyna (Respectus Philologicus, 2012)
This article discusses the identity of a word as a synthetic lexical unit, i.e., a language sign. It also makes an attempt to interpret Ferdinand de Saussure’s theory as presented in his book De l’essence double du langage. According to this theory, a sign of linguistic activity consists of a language sign and a speech sign. The language sign includes an invariant (constant) meaning and an invariant form, while the speech sign is made up of the current meaning (or meanings) as well as the current form. All these elements are interrelated in a way which enables humans to use them in linguistic activity. They constitute a homogeneous, yet non-isomorphic entirety, as they belong to “different worlds.” Despite the complexity of its inner structure, a sign of linguistic activity acquires its identity only due to the coexistence of all its elements (hence the “unity of disunity” of the title). The given theory differs significantly from the bilateral concept of a language sign attributed to Saussure after the publication of A Course in General Linguistics by Albert Sechehaye and Charles Bally. The concept of language sign has developed into the concept of language activity, which includes both invariant elements (of the language system) and current elements (of speech). However, such a concept was first expressed in the unfinished and unedited book De l’essence double du langage by de Saussure. The theory described in de Saussure’s book has been thoroughly analysed by the author of this article. The most important conclusion drawn from this analysis is that a sign of linguistic activity is a complex item, within which the conflict does not result from the connection of mental and physical beings, but rather from the fact that a sign is built of elements belonging to different systems, governed by different laws; the conflict here is neutralized and has a creative rather than a destructive role. The review of the better and less well-known concepts of the language sign proves that this issue has been intriguing philosophers and linguists ever since. In all the theories there are two elements to be noticed: the opposition or conflict, and the attempt to neutralize it, together with the observation that language is an unusual, amazing phenomenon. Surprisingly, it is conflict (no matter what its nature is) that turns out to be the factor that strengthens, if not actively drives, the very existence of a language.